2014
DOI: 10.17140/prrmoj-1-103
|View full text |Cite
|
Sign up to set email alerts
|

Αlpha-1 Antitrypsin Gene Polymorphism in the Egyptian Population: Association with Obstructive Lung Diseases

Abstract: Background: Given the potential adverse effects of asthma and Chronic Obstructive Pulmonary Disease (COPD), this study was undertaken to explore Alpha-1 Antitrypsin (AAT) polymorphism in the Egyptian population and its role in the development and/ or progression of asthma and COPD. The identification of IL-10 as a potential modifier gene for COPD susceptibility provided insight into additional inflammatory pathways to consider in AAT deficiency. Methods: This study was carried on 90 unrelated Egyptians; 37 ast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…The increased frequency of mutant genotype alleles among workers with high BPDE-Alb adduct levels may be attributed to the ability of PAHs metabolites to bind to cellular proteins and DNA, resulting in cell damage and mutations (Ramesh et al 2010). A previous study on Egyptian asthmatic patients reported that the highest frequency of mutant A1AT allele was found in the patients compared to healthy control (Daabis et al 2014). Interestingly, our study was the first study that describes the association between A1AT gene mutation and the levels of PAHs adducts in exposed workers.…”
Section: Discussionmentioning
confidence: 99%
“…The increased frequency of mutant genotype alleles among workers with high BPDE-Alb adduct levels may be attributed to the ability of PAHs metabolites to bind to cellular proteins and DNA, resulting in cell damage and mutations (Ramesh et al 2010). A previous study on Egyptian asthmatic patients reported that the highest frequency of mutant A1AT allele was found in the patients compared to healthy control (Daabis et al 2014). Interestingly, our study was the first study that describes the association between A1AT gene mutation and the levels of PAHs adducts in exposed workers.…”
Section: Discussionmentioning
confidence: 99%